1984
DOI: 10.1016/0014-5793(84)81245-4
|View full text |Cite
|
Sign up to set email alerts
|

Human glucagon‐like peptides 1 and 2 activate rat brain adenylate cyclase

Abstract: Two human glucagon-like peptides, GLP-1 and GLP-2, which are coencoded with pancreatic glucagon in the preproglucagon gene, do not significantly inhibit ['ZSI]monoiodoglucagon binding to rat liver and brain membranes and do not activate adenylate cyclase in liver plasma membranes. Nevertheless, GLP-1 and GLP-2 were each found to be potent stimulators of both rat hypothalamic and pituitary adenylate cyclase. Only 30-50 pM concentrations of each peptide elicited half-maximal adenylate cyclase stimulation. Our da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
41
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 18 publications
7
41
0
Order By: Relevance
“…Only few data [7,8] have been reported on biological effects of GLP-1 and GLP-2 which were characterized structurally as nudeotide sequences. The physiological significance of these findings remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only few data [7,8] have been reported on biological effects of GLP-1 and GLP-2 which were characterized structurally as nudeotide sequences. The physiological significance of these findings remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…This fact most probably explains the glucagon-and GIP-like action of the peptide on pancreatic islets. However, with regard to the N-terminal extension of GLP-1 beyond the glucagon-like sequence it appears unlikely that the action of GLP-1 is mediated through glucagon receptors [18]; in fact, it has been shown that GLP-1 does not bind to glucagon receptors in the liver [7], so one can speculate that GLP-1 may act on its own or on the GIP-receptor on the pancreatic B-cell which has been recently identified [19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The GLP-1 sequence is identical in hamster, man, ox and rat [2] and this high degree of sequence conservation suggests that GLP-1 has a significant biological role which has yet to be determined. Apart from its weak insulinotropic effect [3], the only known actions of GLP-1 are its binding in the hypothalamus and pituitary and the subsequent adenylate cyclase activation [4,5]. While GLP-1 is the major processed form found in the pancreas a smaller fragment GLP-1 7-36 NHz predominates in the intestine [6].…”
Section: Introductionmentioning
confidence: 99%